Dietary Intake, Body Composition and Iron Status in Experienced and Elite Climbers - Gibson-Smith, Edward; Storey, Ryan; Ranchordas, Mayur (Frontiers in Nutrition, 2020)
Climbing has developed into a popular recreational and elite sport, evidenced by a growing number of licenced competition athletes and the acceptance into the Olympic calendar for Tokyo 2020. A nutritional assessment, including the evaluation of anthropometric and biochemical data, has not been previously reported in climbing athletes. Therefore, the aim of this study was to assess the dietary intake, body composition, and iron status in experienced climbers, across a range of performance levels. Forty climbers (n = 20 male, n = 20 female; BMI 21.6 ± 1.7) aged 18-46 participated in the study. Dietary intake was recorded in a 3-day diet diary. Body composition was assessed using a skinfold profile and iron status via blood markers. Mean energy intake was 2154.6 ± 450 kcal·day-1, with 30% of male climbers and 5% of female climbers failing to meet predicted resting energy requirements. Furthermore, 77.5% of participants failed to meet a predicted energy requirement to support a ‘moderate’ training programme. There were no significant correlations between daily energy intake and exercise volume. Mean intake of carbohydrate, protein and fat was 3.7 ± 0.9 g·kg-1·day-1, 1.6 ± 0.5 g·kg-1·day-1 and 1.4 ± 0.4 g·kg-1·day-1 respectively, with no significant difference between genders. Approximately 17% of males (n =3) and 45% of females (n=9) had a sub-optimal iron status. Thirty percent of females met the classification criteria for iron deficiency. Mean serum ferritin was significantly greater in males, compared to females (102.7 ± 54.9 vs 51.4 ± 24.2 μg·L-1; p = <0.01) and significantly lower in vegan/vegetarians vs omnivores, in female climbers only (33.2 ± 14.8 vs 57.5 ± 24 μg·L-1; p = 0.05). No significant differences were observed between climbing ability groups (intermediate-advanced/elite-higher elite) for body composition, dietary intake, or iron status, for males or females. These findings suggest that experienced climbers are at risk of energy restriction and iron deficiency, therefore, routine assessment of nutritional status is warranted. Future research should consider iron status in relation to energy availability and investigate additional factors which may predispose this population to iron deficiency, as well as the risk of relative energy deficiency (RED-S).